Picturesque Trinidad. Tropical Scenery - (:unkn) unknown (The Bonanza, Smith Bros and Co., Trinidad, 2010)
A man stands under huge palms in what appears to be a palm grove. There are about 200 currently known genera of palms with over 2500 species. Most of these can be found in tropical, subtropical, and warm temperate climates.
Colour: Sepia; Style: Portrait; Other: Bordered; Divided
Keywords: Trinidad and Tobago; Postcards; Palms--Trinidad and Tobago; Men--Trinidad and Tobago; [1912]